Enhancing Stakeholder Capacity for Effective Invasive Species Management in Conservation Areas - Poedjirahajoe, Erny; Mahayani, Ni Putu Diana; Wardhani, Frita Kusuma; Satria, Ryan Adi; Pahlevi, Muhammad Reza (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
One of the ecological challenges in managing conservation areas is the colonization and establishment of alien and/or native plant species, especially after forest disturbances. The capacity stakeholders to determine the invasiveness risk of these plant species groups and then management strategies to monitor changes in vegetation structure and species composition is critical. The community engagement program aims to improve the capacity of conservation area stakeholders to identify plant species, including invasive species, and assess the risk of invasive species. Focus group discussion (FGD) were conducted online and offline and targeted stakeholders of the Natural Resources Conservation Agency (Balai Konservasi Sumber Daya Alam–BKSDA) of Central Java Province. Three FGD sessions were held on the topics: (1) forest monitoring and invasion ecology, (2) plant species identification and invasive species monitoring techniques, and (3) vegetation and invasiveness risk analysis. During the discussion, target groups shared ideas and lessons learned related to managing invasive species in the field. The results showed a significant increase in the capacity of the target group (p=4.546e-09), as the average pretest score was 56.25 ± 13.68 compared to the average posttest score of 75.70 ± 20.27. The target group understands the definition of an invasive (alien) species, the factors that determine the success of this species invasion, and the positive and negative contributions alien species to the newly established ecosystem. Some gaps that need to be addressed relate to methods and criteria for identifying species invasiveness in invasive species risk analysis. As a follow-up, a practical training on invasive (alien) species risk analysis was conducted at different occasion and funding sources.